Application of Knowledge Management in The Sudanese Universities: An Analytical Study - Elzain Elkhalefa Elkhder; Bannaga Taha Al-Zubair; El-Rusheed Habboub Mohammed; Saifaldin Idris Onia (Indonesian Journal of Education and Social Studies, 2022)
Knowledge management (KM) is becoming a very important issue in higher education, which drives the ability to collect and analyze information, transform knowledge and apply novelties. Therefore, this paper aimed at introducing a framework of thoughts for applying knowledge management in the Sudanese universities, depending on the analysis of the theoretical studies and the available literature related to the topic. In doing so, the researchers followed a qualitative and analytical type of research. To collect data, previous studies and papers, especially those related to higher education institutions are reviewed. The paper covered the basic concepts, definitions, justifications, and domains, besides the application of (KM) in the Sudanese universities. The main factors that can help in relieving difficulties facing (KM) are also discussed. The paper concluded that Sudanese Universities are considered the most suitable institutions to apply (KM), as they have a strong infrastructure that is favorable to the production and application of knowledge through the venues of investment in scientific research. The paper recommended the utmost necessity of adopting (KM) in the Sudanese universities as an approach to developing the individual and the official administrative to improve the level of outputs and to increase its capacity to adapt to all the prevalent changes and challenges. The use of knowledge management, according to this paper's inference, promotes staff members to advance both themselves and their universities by using this information to scientific research and studies.